Antimicrobial activity of the hydroalcoholic extract of Piper angustifolium (Piperaceae) on Proteus mirabilis - Zavaleta-Espejo, Gina (2019)
The aim of the present investigation was to determine the antimicrobial activity of different concentrations of hydroalcoholic extract of Piper angustifolium “matico” leaves on the growth of Proteus mirabilis under laboratory conditions. To obtain the hydroalcoholic extract of P. angustifolium leaves, Soxhlet equipment with 95% ethyl alcohol was used; dilutions were made with Tween 80 (10, 15, 20, 25 and 30 mg / ml). To evaluate the microbial activity of the extract, the Kirby-Bauer method with 0.7 mm Watman No. 4 paper discs was used, using five discs for each of the concentration, using ciprofloxacin as a positive control and a negative control (Tween 80), the plates were incubated at 37 ° C for 24 hours, after which time the diameters (mm) of the inhibition zones were measured. The highest inhibition halo (18.7 mm) was obtained at the highest concentration, finding a directly proportional effect between the concentration of the extract and the antimicrobial activity. The results showed significant differences between the different concentrations used.